Novel EBV LMP-2-affibody and affitoxin in molecular imaging and targeted therapy of nasopharyngeal carcinoma - Zhu, Shanli (PLoS Pathog, 2020)
Epstein-Barr virus (EBV) infection is closely linked to several human malignancies including endemic Burkitt’s lymphoma, Hodgkin’s lymphoma and nasopharyngeal carcinomas (NPC). Latent membrane protein 2 (LMP-2) of EBV plays a pivotal role in pathogenesis of EBV-related tumors and thus, is a potential target for diagnosis and targeted therapy of EBV LMP-2(+) malignant cancers. Affibody molecules are developing as imaging probes and tumor-targeted delivery of small molecules. In this study, four EBV LMP-2-binding affibodies (Z(EBV LMP-2)12, Z(EBV LMP-2)132, Z(EBV LMP-2)137, and Z(EBV LMP-2)142) were identified by screening a phage-displayed LMP-2 peptide library for molecular imaging and targeted therapy in EBV xenograft mice model. Z(EBV LMP-2) affibody has high binding affinity for EBV LMP-2 and accumulates in mouse tumor derived from EBV LMP-2(+) xenografts for 24 h after intravenous (IV) injection. Subsequent fusion of Pseudomonas exotoxin PE38KDEL to the Z(EBV LMP-2) 142 affibody led to production of Z142X affitoxin. This fused Z142X affitoxin exhibits high cytotoxicity specific for EBV(+) cells in vitro and significant antitumor effect in mice bearing EBV(+) tumor xenografts by IV injection. The data provide the proof of principle that EBV LMP-2-speicifc affibody molecules are useful for molecular imaging diagnosis and have potentials for targeted therapy of LMP-2-expressing EBV malignancies.